Serum Prolactin Levels in Psoriasis Vulgaris. (23rd February 2014) - Handjani, Farhad; Saki, Nasrin; Ahrari, Iman; Ebrahimi, Mehdi; Khorrami, Mohammad Mehdi; Nematollahi, Parastoo
Abstract : Background . Psoriasis is a chronic inflammatory skin disease affecting approximately 1–3% of Caucasians. Prolactin has proliferative effects on human keratinocytes, a dominant feature of psoriasis, and it is thought that this hormone may play a role in the pathogenesis of the disease. This study was conducted to confirm or refute these findings in order to better understand the disease pathogenesis. Methods . The subjects were 90 individuals aged between 15 and 47 years. They were divided into three groups of 30 individuals each: psoriatic patients, atopic dermatitis patients, and control group. A questionnaire was filled regarding their demographic and medical history. All of the study subjects underwent venous blood sampling (5 mL), and serum TSH and prolactin levels were checked. Subjects with abnormal TSH were omitted. Results . None of the patients in the study had raised prolactin, and there was no significant difference in the serum prolactin level between patients with psoriasis and atopic dermatitis and the control group. There was no relationship between the severity of psoriasis and serum levels of prolactin. Conclusion . Prolactin does not seem to play a role in the pathogenesis of psoriasis as its serum levels are comparable with atopic dermatitis patients and that of the normal population.